INTEGRATED PRODUCT POLICY IN THE PROCESS OF DEVELOPING THE PRO-ENVIRONMENTAL CONSUMER ATTITUDE IN THE GIVEN EUROPEAN UNION COUNTRIES - Andrykiewicz, Anna (Ekonomia i Prawo. Economics and Law, 2014)
This article offers possibilities to reduce the negative affect industrial products have on the environment, for which products’ life span has significantly shortened within the last twenty years. The influence tools designed by the European Commission within the Integrated Product Policy (IPP) are very effective on institutional entities. They were evaluated through their impact on the consumer attitudes of the Polish, German and Belgian citizens. It was concluded, based on empirical research, that the main criteria in the process of purchase decision-making are quality, price and functionality, but there were also communities identified, for which the social proof criteria is the priority. The pro ecology changes in the educational system for children and youth, as well as the social campaigns promoting the sustainable consumption among the citizens of the European Union will increase the implementation of the IPP. The correlation between the quality, price and environment would be most favorable. The thesis consist of two chapters and a subchapter. The first chapter describes the reasons for creating the IPP, as well as its tools and the level of their implementation. The second chapter brings up the concept of the sustainable consumption, the meaning of the Earth Summit in Rio de Janeiro which was about the environment and the development, and it includes the reference to the documents of the Union. It analyses the role of business and the consumers in the implementation of the sustainable development. The subchapter consists of research on the sustainable consumption conducted on individual consumers.